2020
DOI: 10.1002/lary.29355
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the Antifibrotic Potential of Estradiol for Vocal Fold Fibrosis

Abstract: Objectives/Hypothesis: Vocal fold fibrosis remains a significant clinical challenge. Estrogens, steroid hormones predominantly responsible for secondary sexual characteristics in women, have been shown to alter wound healing and limit fibrosis, but the effects on vocal fold fibrosis are unknown. We sought to elucidate the expression of estrogen receptors and the effects of estrogens on TGF-β1 signaling in rat vocal fold fibroblasts (VFFs).Study Design: In vitro. Methods: VFFs were isolated from 10-week-old, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…The sex hormones affect wound healing. 21,22 Therefore, only male animals were included in this study to exclude hormonal effects. The perforations were performed with a cannula to standardize the NSPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sex hormones affect wound healing. 21,22 Therefore, only male animals were included in this study to exclude hormonal effects. The perforations were performed with a cannula to standardize the NSPs.…”
Section: Discussionmentioning
confidence: 99%
“…We planned this experimental study to investigate the effects of MLT on NSP healing. The sex hormones affect wound healing (21,22). Therefore, only male animals were included in this study to exclude hormonal effects.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[15,17,18] There are differences between the sexes, mainly due to hormonal effects, particularly estrogen, on wound healing. [19] Therefore, only male rats participated in the present study. In our study, we planned to examine the healing parameters of a wound belonging to the nasal septum as it is the formation containing the most different types of tissue in the nasal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Van Lake-based hypertonic alkaline nasal irrigation (HANI) solution is a hypertonic alkaline solution that contains 12 g/L of NaCl, 1.1 g/L of magnesium sulfate heptahydrate (MgSO 4 .7H 2 O), 0.1 g/L of calcium chloride dihydrate (CaCl 2 .2H 2 O), 0.8 g/L of potassium chloride (KCl), 4 g/L of sodium bicarbonate (NaHCO 3 ), and 2 g/L of sodium sulfate (Na 2 SO 4 ), and its pH is 9. In a clinical study, it has been shown that HANI reduces the nasopharyngeal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) load and alleviates the clinic associated with coronavirus disease 2019 (COVID- 19). [1,2] The wound is the disruption of the normal functional anatomy of the tissues due to internal or external causes.…”
Section: Kbb Uygulamalarımentioning
confidence: 99%
“…7 Treatment of scarred VF includes voice therapy, scar excision, localized steroid injection, and biomaterial injection or implantation. 8 Although voice therapy is non-invasive, the duration is usually long and requires the cooperation of patients. Meanwhile, the improvements are not ideal.…”
Section: Introductionmentioning
confidence: 99%